2019
DOI: 10.52434/janhus.v3i2.606
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH SUBSTITUSI BUNGKIL KEDELAI DENGAN Indigofera zollingeriana HASIL FERMENTASI TERHADAP SIFAT FISIK PELLET SETELAH MASA PENYIMPANAN SATU BULAN (Effect Of Soybean Meal Substitution With Indigofera Zollingeriana Fermented Products On Physical Properties Of Pellets After One Month Storage Period)

Abstract: Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh dari substitusi bungkil kedelai dengan Indigofera zollingeriana hasil fermentasi terhadap sifat fisik pellet setelah masa penyimpanan satu bulan. Penelitian uji sifat fisik pellet dilaksanakan pada bulan April sampai September 2018 yang bertempat di Laboratorium terpadu Fakultas Pertanian UNIGA. Metode yang dilakukan yaitu Metode Eksperiental menggunakan Rancangan Acak Lengkap (RAL) dengan 5 perlakuan dan 4 ulangan, yaitu : R0 = Bungkil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…The difference in pellet density might be due to the varied ability of starch and lignin contained in each binder to bind the Indigofera flour during pellet production. The Indigofera pellet density obtained in this research is higher than Indigofera pellet observed in Febrianti et al [18] which ranged from 1.05 -1.18 gcm-3, but lower than Gliricidia pellet observed in Royani and Herawati [17] which ranged from 1.66 -2.00 gcm-3.…”
Section: Densitycontrasting
confidence: 68%
“…The difference in pellet density might be due to the varied ability of starch and lignin contained in each binder to bind the Indigofera flour during pellet production. The Indigofera pellet density obtained in this research is higher than Indigofera pellet observed in Febrianti et al [18] which ranged from 1.05 -1.18 gcm-3, but lower than Gliricidia pellet observed in Royani and Herawati [17] which ranged from 1.66 -2.00 gcm-3.…”
Section: Densitycontrasting
confidence: 68%